Uniportal Thoracoscopic Debridement for Children With Refractory Pleural Empyema: Case Series of 21 Patients - Huang, Jin-Xi; Chen, Qiang; Hong, Song-Ming; Hong, Jun-Jie; Cao, Hua (Frontiers in Pediatrics, 2021)
Purpose: The effectiveness of video-assisted thoracic surgery (VATS), even uniportal VATS (U-VATS), in the treatment of pleural empyema has recently been demonstrated. However, few works have evaluated its safety and feasibility for children. We review our experience with U-VATS in the treatment of pleural empyema for children under 11 years old. Methods: From January 2019 to December 2020, we consecutively enrolled 21 children with stage II and stage III pleural empyema in our institution. A 1.0 cm utility port was created in the 5th intercostal space at the anterior axillary line. A rigid 30°5 mm optic thoracoscope was used for vision, and two or three instruments were used through the port. Surgery was based on three therapeutic columns: removal of pleural fluid, debridement, and decortication. A chest tube was inserted through the same skin incision. Perioperative data and outcomes were summarized. Results: The procedures were successful, and satisfactory debridement of the pleural cavity was achieved in all cases. The mean age was 4.1 years (range: 6 months to 11 years old). The mean operating time was 65.7 ± 23.2 min. No intraoperative conversion or major complications were identified among the patients. The mean hospital stay was 5.0 ± 0.6 days. At a follow-up of more than 4 months after operating, all patients had recovered well without recurrence. Conclusion: According to our experience, U-VATS debridement is feasible for the surgical management of stage II and III empyema in the pediatric population. Indeed, U-VATS permits easier performance and complete debridement and decortication, with a very low risk for conversion.